Marble columnar sarcophagi in the context of the Arsacids palace residence in Garni - Margaryan , Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
The palace complex of the Arsacids was opened in Garni in 1952-1953. About 70 pieces of marble lay on the floor of the second room in the southeastern half of the palace. The collection consists of pieces of two types. Small in size, architecturally decorated and sculptural fragments belong to the Asia Minor columnar sarcophagi ‘Sidamarа’ of the 2nd-4th centuries. The rite of burial in marble sarcophagi of the Hellenistic-Roman style reflects the features of the culture of the ruling elite of Armenia during the late Arsacids. Larger architectural details are parts of the decoration of the building. The fragments of both groups belonged to one of the buildings of the palace, expanded by Trdat III was formed in front of the temple – a royal residence from several buildings, completed by a bath, close to the complexes of Roman Asia Minor and Syria. The structure of the royal fortress with a residence in Garni is similar to the residences and large centers of Armenia in late antiquity – early Middle Ages (in Vagharshapat, Dvin, Zvartnotz, Aruch, etc.).